Effects of lactic acid and lauricidin on the survival of Listeria monocytogenes, Salmonella enteritidis and Escherichia coli O157:H7 in chicken breast stored at 4°C - Anang, Daniel Mensah; Rahmat Ali, Gulam Rusul; Bakar, Jamilah; Foo, Hooi Ling (Elsevier, 2007)
Lauricidin and lactic acid were evaluated for their eVects on growth and survival of Listeria monocytogenes (L55), Salmonella enteritidis (S552) and Escherichia coli O157:H7 (E19) inoculated onto raw chicken breast. Fresh, raw chicken breasts were purchased immediately after slaughter and transported on ice to the laboratory within 20 min. Each chicken breast was decontaminated by brieXy dipping in 70% ethanol and passed through a Xame of a Bunsen burner and then allowed to cool. The decontaminated Chicken breast was dipped in TSB broth, at room temperature (25 °C) for 15 min, containing approximately log 9CFU/ml of L. monocytogenes, S. enteritidis or E. coli O157:H7. Initial counts of L. monocytogenes, S. enteritidis or E. coli O157:H7 counts in chicken breast immediately after dipping in TSB broth were in the range of log 7–log 8CFU/g. After inoculation, the chicken breasts were kept at room temperature for 20min to allow attachment. Each inoculated chicken breast (25 °C) was dipped in 0 (control – sterile water), 0.5%, 1%, 1.5% or 2% of lauricidin (w/v) or lactic acid (v/v) for 10, 20 or 30min and then individually placed in oxygen-permeable polyethylene bags. Breasts were subjected to microbiological analyses after treatment (day 0) and after storage for 2, 5, 7, 10 and 14 d at 4 °C. Initial counts of L. monocytogenes, S. enteritidis and E. coli O157:H7, in chicken breast treated with lauricidin decreased by 2.90, 1.31 and 2.27 logCFU/g, respectively. Lauricidin was more eVective in reducing L. monocytogenes population than S. enteritidis and E. coli O157:H7 population. Dipping chicken breast in lauricidin for 30min caused a signiWcant reduction of L. monocytogenes, S. enteritidis and E. coli O157:H7 population compared to 10 and 20min dipping. Initial L. monocytogenes, S. enteritidis and E. coli O157:H7 counts on chicken breast treated with lactic acid decreased by 1.97, 1.71 and 2.59 logCFU/g, respectively. Lactic acid caused a higher reduction in initial S. enteritidis and E. coli O157:H7 counts compared to lauricidin.